2016
DOI: 10.1080/09500693.2016.1196843
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Rasch measurement model to explore the relationship between content knowledge and topic-specific pedagogical content knowledge for organic chemistry

Abstract: Research has shown that a high level of content knowledge (CK) is necessary but not sufficient to develop the special knowledge base of expert teachers known as pedagogical content knowledge (PCK). This study contributes towards research to quantify the relationship between CK and PCK in science. In order to determine the proportion of the variance in PCK accounted for by the variance in CK, instruments are required which are valid and reliable as well as being unidimensional to measure person abilities for CK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 29 publications
3
19
0
1
Order By: Relevance
“…Yet, the moderate nature of the correlation suggests some divergence, indicating they are likely measuring distinct aspects of science knowledge. Similar findings in terms of moderate correlations between measures of science teachers' subject matter knowledge and measures designed to assess these practice-based aspects of CKT more closely have been reported in the literature (Davidowitz & Potgieter, 2016;Grobschedl, Harms, Kleickmann, & Glowinski, 2015;Mikeska, Phelps, & Croft, 2016). Additional research, especially the use of cognitive interviews, would be useful for better understanding this relationship and the knowledge and reasoning that teachers use as they respond to these CKT science items.…”
Section: Discussionsupporting
confidence: 83%
“…Yet, the moderate nature of the correlation suggests some divergence, indicating they are likely measuring distinct aspects of science knowledge. Similar findings in terms of moderate correlations between measures of science teachers' subject matter knowledge and measures designed to assess these practice-based aspects of CKT more closely have been reported in the literature (Davidowitz & Potgieter, 2016;Grobschedl, Harms, Kleickmann, & Glowinski, 2015;Mikeska, Phelps, & Croft, 2016). Additional research, especially the use of cognitive interviews, would be useful for better understanding this relationship and the knowledge and reasoning that teachers use as they respond to these CKT science items.…”
Section: Discussionsupporting
confidence: 83%
“…With respect to this claim, Friedrichsen et al (2009) have argued that teaching experience plays a critical role in PCK development by further facilitating the integration among PCK components. In a study conducted by Davidowitz and Potgieter (2016), it was determined that subject matter knowledge was not the only determinant of an improved and integrated PCK. Accordingly, it was observed that teachers with a low level of subject matter knowledge also had a low level of PCK; however, the PCK of teachers with a high level of subject matter knowledge was not always high, and the value of experience emerges at this point.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Teacher's science SMK is foundational for other forms of teacher knowledge, such as PCK (Abell, ; Chan & Yung, ; Davidowitz & Potgieter, ; Rollnick et al, ; van Driel et al, ). For example, Chan and Yung () found the PCK development of four Hong Kong biology teachers was facilitated by strong SMK and limited when teachers had weak SMK.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies have explored shorter term teaching experiences during teacher preparation with similar results (Cisterna, Hanuscin, & Lipsitz, ; Gess‐Newsome & Lederman, ), finding that “Teaching experience alone was not enough to facilitate learning ‘on the job,’ calling into question the simple assumption that teachers automatically learn from experience” (Gess‐Newsome & Lederman, , p. 313). Cross sectional studies have also found teaching experience does not necessarily lead to improvements in teachers' SMK (Davidowitz & Potgieter, ; Hoz et al, ; Kleickmann et al, ; Nowicki et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%